Measuring the Transparency of MSME Financial Reports: Evaluation of SAK EMKM Implementation at Toko Ide Elektronik in Surabaya - Jeanne Asteria Wawolangi; Sephiana Ayu (Universitas Katolik Darma Cendika, 2025)
This study aims to describe and reconstruct the financial statements of an MSME, Toko Ide Elektronik in Surabaya, in accordance with the Financial Accounting Standards for Micro, Small, and Medium-Sized Entities (SAK EMKM) issued by the Indonesian Institute of Accountants. The research was motivated by the fact that the entity only kept simple cash-based records, did not separate business and personal transactions, and had not yet prepared structured reports such as a statement of financial position, statement of profit or loss, and notes to the financial statements. Using a descriptive qualitative approach, data were collected through interviews, observation, and documentation of 2023 transactions, then mapped into the SAK EMKM reporting format. The results show that the application of SAK EMKM allows MSMEs to present more reliable and comparable financial information, especially through the recognition of inventories, fixed assets, and monthly depreciation expenses, so that business performance and financial position can be measured more accurately. In addition, standardized reports increase accountability to external parties (banks, tax authorities, and business partners) and support better decision making by the owner. This finding confirms that SAK EMKM is an appropriate, simple, and implementable standard for MSMEs that have limited accounting literacy and human resources.